Arahan Peningkatan Prioritas Kinerja Operasional Stasiun Sidoarjo dan Stasiun Indro Menggunakan Analisis QFD - Hariyani, Septiana; Agustin, Imma Widyawati; Lubis, M Fachri Rasidi (Indonesian Journal Publisher, 2024)
The Gerbangkertosusila area is designated as the main driver of the regional economy (primer mover) which has the criteria as an area that grows faster than other regions in a province. Sidoarjo and Gresik Regency are two areas included in the seven administrative areas of Gerbangkertosusila. Sidoarjo and Gresik have transportation systems that can support the mobility of the surrounding community, namely Sidoarjo Station and Indro Station. Sidoarjo Station and Indro Station still have performance that needs to be improved such as the size of the room area and supporting installation devices that do not meet the standards and there is still crossing in the station circulation. The purpose of this study is to determine the priority of directions for improving the operational performance of Sidoarjo Station and Indro Station. This research uses Quality Function Deployment (QFD) analysis. The priority of the direction to improve the operational performance of Sidoarjo Station and Indro Station is determined based on the value of Absolute Importance (AI). The results of the analysis show that the priority direction for improving the operational performance of Sidoarjo Station is the provision of TV as an audio-visual information medium (8,100), while the priority for the direction to improve the operational performance of Indro Station is the addition of information boards for the station area name (9,643).